2008
DOI: 10.1182/blood-2007-06-095331
|View full text |Cite|
|
Sign up to set email alerts
|

A new prognostic index (MIPI) for patients with advanced-stage mantle cell lymphoma

Abstract: There is no generally established prognostic index for patients with mantle cell lymphoma (MCL),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
506
2
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 811 publications
(526 citation statements)
references
References 40 publications
(64 reference statements)
10
506
2
8
Order By: Relevance
“…As observed in numerous previous studies, 23,[51][52][53][54][55][56] OS was found to be slightly lower in patients ⩾ 55 years without reaching any statistical significance in uni-and multivariate analysis. However, of greater clinical interest is that (1) the documented difference was so small that neither univariate nor multivariate analysis could reveal a significant impact of patient age on OS; and (2) stable plateaus for OS were reached for both subgroups, suggesting potential cure rates of 50% for younger and 42% for elderly patients (cf.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As observed in numerous previous studies, 23,[51][52][53][54][55][56] OS was found to be slightly lower in patients ⩾ 55 years without reaching any statistical significance in uni-and multivariate analysis. However, of greater clinical interest is that (1) the documented difference was so small that neither univariate nor multivariate analysis could reveal a significant impact of patient age on OS; and (2) stable plateaus for OS were reached for both subgroups, suggesting potential cure rates of 50% for younger and 42% for elderly patients (cf.…”
Section: Discussionsupporting
confidence: 59%
“…The median follow-up of surviving patients was 9.1 years (range 3.6-15.7). The Kaplan-Meier estimates for OS 1, 2, 5 and 10 years after HCT (95% confidence interval) were 67% (63-71), 60% (56-64), 53% (49-58) and 48% (44)(45)(46)(47)(48)(49)(50)(51)(52). The corresponding estimates for EFS were 63% (59-67), 53% (49-58), 47% (42-51) and 40% (36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Conditioning Regimensmentioning
confidence: 91%
“…The MIPI has been validated and refined for previously untreated patients who received chemotherapy ± rituximab (Hoster et al , 2008, 2014). In our analysis, some but not all of the MIPI‐based factors were identified here as having a significant impact on PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, MCL has an aggressive clinical course that is resistant to therapy, with a mean survival of 3 years. 5 Recognition of MCL and its differentiation from other non-Hodgkin's lymphoma subtypes is important because of this poor prognosis and changing therapeutic regimens. …”
Section: Discussionmentioning
confidence: 99%